Are Adverse Childhood Experiences Associated With Deficits in Self-Control? A Test Among Two Independent Samples of Youth. (February 2020) - Meldrum, Ryan C.; Campion Young, Brae; Soor, Sadhika; Hay, Carter; Copp, Jennifer E.; Trace, Madison; Smith-Darden, Joanne P.; Kernsmith, Poco D.
A large body of research links both a lack of self-control and adverse childhood experiences (ACEs) to a variety of negative health and behavior outcomes, including delinquent and criminal behavior. To date, relatively little research considers whether experiencing a greater variety of ACEs is associated with lower self-control. We advance this area of research by first articulating potential mechanisms through which ACEs may impact self-control. We then investigate whether experiencing more ACEs is inversely associated with self-control in separate samples of youth from Michigan and Florida. For both samples, results indicate that experiencing a greater variety of ACEs is negatively associated with self-control. Exploratory analyses also indicate that ACEs reflecting interpersonal maltreatment are more strongly associated with deficits in self-control than ACEs pertaining to aspects of household dysfunction.